Pengaruh Gaya Kepemimpinan, Kompensasi dan Lingkungan Kerja terhadap Disiplin Kerja Pegawai pada Kantor Badan Perencanaan Penelitian dan Pengembangan Daerah (BAPPEDA) di Kota Padang Panjang - Emma Zurrianti; Yulihasri Yulihasri (STIE AMKOP, 2023)
The objective of this study was to investigate the relationships between leadership style, compensation and work environment on work discipline within the context of the Regional Research and Development Planning Agency Office of Padang Panjang City. The total population in this study was 42 people as well as being the sample in this study using saturated samples or the census method. Data was collected by distributing questionnaires with a Likert scale model and then being tested for the validity and reliability of the questionnaire. The data analysis technique used is the Smart PLS method. The purpose of this study is to see the relationship between the effect of the independent variables on the dependent variable. The results of this study are a). Leadership style has a positive and significant influence on Work Discipline at the Regional Research and Development Planning Agency Office of Padang Panjang City b). Compensation Ability has a positive and significant influence on Work Discipline at the Regional Research and Development Planning Agency Office of Padang Panjang City. c). The work environment has a positive and significant influence on Work Discipline at the Regional Research and Development Planning Agency Office of Padang Panjang City. Keywords: Leadership Style, Compensation, Work Environment, Discipline